Antagonism of Two Trichoderma Species against Alternaria alternata on Capsicum frutescens - Pandey*, Adarsh (Journal of Experimental Sciences, 2010)
<div style="border-right: medium none; padding-right: 0in; border-top: windowtext 1pt solid; padding-left: 0in; background: white; padding-bottom: 0in; border-left: medium none; padding-top: 1pt; border-bottom: medium none; mso-element: para-border-div; mso-border-top-alt: solid windowtext .5pt;"> Abstract Biological management of plant disease is a much popular method of disease control now a days. Being ecofriendly safe and effective disease control agents, biocontrol agents are being used widely by farmers in combating disease and pests. The present investigation deals with comparative antagonistic behavior of two different species of Trichoderma viz. Trichoderma harzianum and Trichoderma viride against Alternaria alternata, a common and destructive pathogen of Capsicum frutescens. To find out the comparative antagonistic properties of both the species of Trichodema against Alternaria alternata, culture plate technique was used and the experiment was allowed to run for 10 days. Results indicated that Trichoderma harzianum which reduced the growth of Altrnaria alternata by 67.07% is more effective in controlling the growth of test pathogen. Trichoderma viride, causing a reduction of 66.67% was also found to be a suitable biocontrol agent. Key words: Capsicum frutescens, Trichoderma, Biocontrol, Alternaria alternate, Antagonism Department of Botany, S. S. (P. G.) College, Shahjahanpur, U. P., India Please Cite This Article As: Adarsh Pandey. 2010. Antagonism of Two Trichoderma Species against Alternaria alternata on Capsicum frutescens. J. Exp. Sci. 1(5):18-19.